MP008: Quick to be seen; quick to come back: does first visit CTAS-category predict admission for unplanned returns?. (2nd June 2016) - Lewis, D.; Atkinson, P.R.; Fraser, J.; Howlett, M.
Abstract : Introduction: The percentage of unplanned return visits (URV) to the Emergency Department (ED) within 48 or 72 hours of discharge that result in an admission to hospital has been recommended as the top Canadian ED patient safety quality indicator. International data exists although inconsistences exist in the way URV are defined and measured. To our knowledge there are no published Canadian data on the percentage of ED URV admissions. This study examines our own URV data and in particular the correlation between URV admission rates and first visit Canadian Triage Acuity Scale (CTAS) category.Methods: A retrospective analysis of 12-month's data (January - December 2015) was completed for URV to the ED of a 445 bed regional tertiary care adult and pediatric teaching hospital with 57, 000 annual attendances. URV was defined as any patient registering within 72 hours of an earlier visit that had resulted in a discharge from ED. Planned return visits were excluded. The data was analysed for an overall URV percentage, UV percentage by first visit CTAS category, overall percentage of URV admitted and URV admission percentage by first visit CTAS category. Pearson R correlation and Fishers Exact Test were used to test the relationship.Results: During the 12-month period there were 57, 025 registrations of which 46, 793 patients were discharged. There were 3566 URV (7.62% of those discharged); the number of URV admitted was 532 (1.14 % of those discharged). The return rate/admission rates by CTAS category were: CTAS 1: 6.74%/1.55%; CTAS 2: 7.86%/1.92%; CTAS 3: 8.54%/1.35%; CTAS 4: 5.99%/0.40%; CTAS 5: 5.55%/0.27%. The RR of admission on return for discharged CTAS groups 1 and 2, compared with CTAS 3, 4 and 5 was 1.90 (95 CI 1.57 to 2.30; p<0.0001). Rate of admission on return was negatively correlated with initial CTAS level (Pearson r = -0.89 (95 CI -0.99 to -0.03); R 2 =0.79; F=11.25; p=0.04).Conclusion: We have demonstrated a relationship between first visit CTAS category and the unplanned return admission rate. If admission is taken as a marker of illness severity, then the likelihood of an inappropriate discharge is inversely proportional to first visit CTAS score. While this makes sense intuitively, our data confirms this relationship in a Canadian tertiary care hospital and supports the reporting of ED URV admission data by first visit triage category as an important quality indicator.